Avaliação da rugosidade superficial de restaurações estéticas e do esmalte adjacente após o uso de diferentes instrumentos rotatórios de acabamento e polimento - Silva, Regina Célia Santos Pinto [UNESP] (1997)
The purpose of this in vitro study was to evaluate the surface texture of two aesthetic restorative materials: a composite resin TPH (Dentsply) and a polyacid-modified composite VariGlass (Dentsply). as well as the adjacent enamel to these restorations, after polishing and finishing procedures with diamond points, with eight and twelve blade trimming and finishing burs, with a green silicone tip, with a diamond polishing past and with an association of the last two procedures. We have selected 114 teeth, six of wich received neither polishing nor finishing procedures, with the purpose of evaluating the enamel roughness. The remaining teeth received cavity preparations on the buccal surfaces and were restored following the manufacture' s instructions. The specimens were kept for 24 hours in destiled water at 37° C and only then polishing and finishing procedures were performed. Profilometric analyses were carried out using a Perthometer S8P (Perthen, Mahr, Germany) and the collected data were statísticaly analysed. The results showed that the composite resin presented less surface roughness than the polyacid-modified composite, that the enamel adjacent to the restorations became smoother than the sound enamel; that the eight and twelve blade burs promoted surfaces less roughen than the diamond points, with statisticaly meaningful difference. None of the finishing and polishing procedures demonstrated to be satisfactory for the glass ionomer cement. Researches concerning the finishing and polishing of this material are necessary, as well as the material itself: so that better surface texture restorations could be obtained